Fenomena Kesurupan dalam Agama Islam - Biantoro, Oktio Frenki (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2021)
Trance is a condition in which a person is mentally disturbed and loses control over themselves, resulting in them not understanding what they are saying, losing their memory, and feeling confused. This research is included in the type of library research or library research, where researchers read, study, and analyze relevant literature, such as the Qur'an, hadith, books, and the results of previous research. The literature approach allows researchers to gain an in-depth understanding of the topic under study through careful review and study of the various available text sources. The phenomenon of trance has occurred since the time of the Prophet Muhammad SAW, as in the hadith about a woman who came to complain to the Prophet about her possession, namely a disorder that causes tension in the body and can even cause fainting, similar to epilepsy. This type of possession can be caused by disturbances from jinns, both due to the actions of sorcerers and other disturbances. Jin has the potential to affect the human body and feelings. In Islam, to protect oneself from the influence of negative jinn, it is important to practice the actions taught in the religion, such as memorizing and reciting the Ayat Kursi, adhering to the dhikr and prayers of the Prophet Muhammad, and avoiding daydreaming and over-eating.